Thermal characteristics of combined compressor - ejector refrigeration/heat pump systems for HVAC&R - Gjerasimovski, Aleksandar; Sharevska, Maja; Gjerasimovska, Natasha; Sharevska, Monika; Filkoski, Risto (National Library of Serbia, 2023)
Thermal characteristics of combined compressor - ejector refrigeration/heat pump systems applied in heating, ventilation, air conditioning and refrigeration (HVAC&R) of buildings are investigated. An original model for estimation of the thermal characteristics of the combined cycles is developed, to determine the influence of the evaporation, interstage, condensation, and generating temperature conditions on mechanical and thermal COPs of the combined system, and to optimize the thermal parameters of the cycle. Results are presented for different temperature conditions, with R134a as a suitable refrigerant. A comparison between the thermal characteristics of the simple mechanical vapor compression cycle, the simple ejector thermocompression cycle, and the combined compressor - ejector refrigeration / heat pump cycle is given. The benefits of implementation of combined compressor - ejector refrigeration/heat pump cycles in HVAC&R systems are discussed. The temperature lift or temperature difference between condensing temperature and interstage temperature significantly influences the thermal (ejector) coefficient of performance. If temperature lift is between 10 K and 20 K, high values of thermal COPs can be achieved (0.5÷1.0, for generating temperature equal to 80ºC; 1.0÷1.8, for generating temperature equal to 120ºC); If temperature lift is between 30 K and 40 K, very low values of COPth can be obtained (0.05÷0.3). High values of mechanical COPs can be achieved (24.8÷6.9), for compressor stage temperature lift 10÷30 K.
Keywords: energy efficiency, compressor, ejector, thermocompression, HVAC&R, refrigeration, heat pump